Inter-level explanation: the case of neuropsychoanalysis. - Gabriel, Rami (Synthese, 2025)
This paper develops theory of inter-level explanation by exploring how neuropsychoanalysis draws together psychodynamic and neuroscientific methodological approaches. I reflect on concepts in the philosophy of science to suggest that integration of levels of analysis may be possible without reduction. This scheme is illustrated by describing empirical work on the neuroscience of pleasure and desire in the dopamine motive system. Towards the goal of integrating context into mosaic explanation, I discuss how objects come to carry an affective aura through conditioned learning. This emotional apperception develops into a learned motivating sensitization, which is experienced as liking, or desire to seek. While the neurosciences pursue mechanistic explanations, psychodynamic theory frames these processes through narrative and discourse. These two approaches can be integrated through intra and inter-level constraints. I illustrate pluralistic non-reductionist explanation through the example of affective psychodynamics of pleasure in drug use.